Sclerosing stromal tumor of the ovary: a rare case report - Atay, Arif Onur; Atay, Feride; Akdemir, Ali; Serin, Gurdeniz; Zekioglu, Osman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Sclerosing stromal tumors (SST) are rare benign tumors of the ovary, accounting for less than 5% of all sex cord-stromal neoplasms. We report the case of a 33-year-old woman who presented with pelvic pain and was found to have a 78×55 mm heterogeneous semisolid mass in the left adnexa on ultrasonography. Pelvic magnetic resonance imaging revealed a well-circumscribed adnexal lesion with both solid and cystic components, raising suspicion for a neoplastic process. The patient underwent laparoscopic left salpingo-oophorectomy. Final histopathological examination confirmed a diagnosis of SST, with an intact capsule and immunohistochemical staining positive for CD31 and CD34, and negative for cytokeratin AE1/AE3, inhibin A, and desmin. The Ki-67 proliferation index was 6%, and peritoneal cytology was benign. This case emphasizes the importance of including this rare tumor in the differential diagnosis of adnexal masses and highlights the value of minimally invasive surgery in their management.